The record 2013 Southern Hemisphere sea-ice extent maximum. Issue 69 (2015) - Reid, Phil; Stammerjohn, Sharon; Massom, Rob; Scambos, Ted; Lieser, Jan
Abstract: Observations of Southern Hemisphere sea ice from passive microwave satellite measurements show that a new record maximum extent of 19.58 x 10 6 km 2 was reached on 30 September 2013; the extent is just over two standard deviations above the 1979-2012 mean and follows a similar record (19.48x 10 6 km 2 ) in 2012. On the record day in 2013, sea-ice extent was greater than the 30 year average (1981-2010) in nearly all Southern Ocean regions. For the year as a whole, Southern Hemisphere sea-ice area and extent were well above average, and numerous monthly and daily records were broken. Analysis of anomaly patterns and the atmospheric and oceanic events suggests that a sequence of regional wind and cold-freshened surface waters is likely responsible for the record maximum and the generally high 2013 extent. In particular, the Ross Sea sector experienced a combination of cold southerly winds associated with the position and depth of the Amundsen Sea low, and lower than normal sea surface temperatures (up to 2°C below normal). The resulting very high anomaly in ice extent in this region was a major component of the overall record maximum.